Optical Filter Bank Modeling and Design for Multi-Color Visible Light Communications - Pengfei Ge; Xintong Ling; Jiaheng Wang; Xiao Liang; Shuo Li; Chunming Zhao (IEEE Photonics Journal)
Multi-color visible light communication (MC-VLC) can achieve a multi-fold rate by taking advantage of multiple color channels. The optical filters for separating different colors are often designed for the normal incidence case only. However, the center wavelength (CWL) of the optical filter shifts as the angle of incidence (AOI) varies, leading to performance degradation. To address the issue caused by the CWL shift, we propose a novel concept of the optical filter bank that uses a group of narrow-band optical filters and divides the whole visible light spectrum into many narrow bands of wavelengths. The optical filter bank can flexibly combine the useful signal of each monochromatic color and effectively avoid the undesired interference, even if the CWL shifts. Based on the optical filter bank, we establish the channel model and signal model of the MC-VLC system, and then jointly design the linear precoding and equalization for MC-VLC. As illustrated by simulations, the proposed optical filter bank transceiver can achieve a high rate and stable performance at varying AOIs.